2019
DOI: 10.1557/adv.2019.278
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Lifetimes and Thermal Conductivity of the Molecular Crystal α-RDX

Abstract: The heat transfer properties of the organic molecular crystal -RDX were studied using three phonon-based thermal conductivity models. It was found that the widely used Peierls-Boltzmann model for thermal transport in crystalline materials breaks down for -RDX. We show this breakdown is due to a large degree of anharmonicity that leads to a dominance of diffusive-like carriers. Despite being developed for disordered systems, the Allen-Feldman theory for thermal conductivity actually gives the best description o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
(48 reference statements)
0
20
0
1
Order By: Relevance
“…which was found to be 0.66 % indicating a consistently good Lorentzian fit of the SED for all modes. We observed that the phonon lifetimes decrease with increasing frequency up to ∼3 THz, followed by flattening and subsequent increase for some higher frequency modes (above ∼9 THz) . This is in contrast to the trend observed in simple atomic crystals like silicon , and carbon nanotubes in which phonon lifetimes monotonically decrease with frequency.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…which was found to be 0.66 % indicating a consistently good Lorentzian fit of the SED for all modes. We observed that the phonon lifetimes decrease with increasing frequency up to ∼3 THz, followed by flattening and subsequent increase for some higher frequency modes (above ∼9 THz) . This is in contrast to the trend observed in simple atomic crystals like silicon , and carbon nanotubes in which phonon lifetimes monotonically decrease with frequency.…”
Section: Resultsmentioning
confidence: 95%
“…We also find that ∼70 % of κ contribution can be attributed to the optical mode phonons, primarily low frequency optical phonons (<4 THz) which are neglected in the CWP model. Higher frequency modes have negligible contribution to κ primarily due to their relatively low diffusivity (phonons with frequency ∼80 THz have diffusivity about five orders of magnitude lower than the phonons with frequency <4 THz) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations